Serum Vitamin D in Patients with Chronic Obstructive Lung Disease Does Not Correlate with Mortality – Results from a 10-Year Prospective Cohort Study - Holmgaard, Dennis Back (Public Library of Science, 2013)
BACKGROUND: Recent studies have found vitamin D (25-OHD) deficiency and insufficiency to be common among patients with COPD. Serum level of 25-OHD seems to correlate to pulmonary function, COPD disease staging, and increased susceptibility to respiratory infections. We wanted to investigate whether vitamin D deficiency or insufficiency was associated with mortality rate in patients suffering from advanced COPD. METHODS: 25-OHD serum levels were measured in 462 patients suffering from moderate to very severe COPD. Patients were stratified into three groups according to serum levels of 25-OHD. Outcome measure was mortality in a 10 year follow-up period. Kaplan-Meier curves (KM) were plotted and mortality hazard ratios (HR) were calculated using Cox Proportional Hazard regression (Cox PH). RESULTS: Serum 25-OHD deficiency and insufficiency were prevalent. We were unable to demonstrate any association between baseline serum levels of 25-OHD and mortality rate. We found an association between mortality and age [HR 1.05 (CI 95%: 1.03–1.06)], Charlson score [HR 1.49 (CI 95%: 1.06–2.09)], increasing neutrophil count [HR 1.05 (CI 95%: 1.02–1.09)], severe [HR 1.41 (CI 95%: 1.06–1.86)]/very severe COPD [HR 2.19 (CI 95%: 1.58–3.02)] and a smoking history of more than 40 pack years [HR 1.27 (CI 95%: 1.02–1.70)]. CONCLUSIONS: Serum level of 25-OHD does not seem to be associated with mortality rate, suggesting no or only a minor role of 25-OHD in disease progression in patients with moderate to very severe COPD.